Sahnya Suatu Perjanjian Berdasarkan Kitab Undang-Undang Hukum Perdata - Ratnaningsih, I Dewa Ayu Sri; Dewi, Putu Eka Trisna (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: This research aims to develop legal knowledge in the field of civil law, especially regarding the validity of agreements. The research also aims to achieve a Bachelor's degree, Master of Laws. Method: The research used in this journal is normative legal research, normative legal research is based on secondary data. Normative legal research is called research that examines rules and norms, as expressed by Sudikno Mertokusomo. In this research, primary legal materials are used, namely the Law (Civil Code), as well as secondary legal materials, namely doctrine, articles, internet information, and finally tertiary legal materials such as dictionaries. These legal materials were collected by conducting document studies until they were collected in accordance with the research objectives. The legal materials obtained, both primary legal materials and secondary legal materials, are analyzed comprehensively based on legal interpretation. Comprehensive means that the analysis is carried out in depth covering various aspects according to the broad scope of the research. Then legal interpretation itself is an interpretation which is one method of legal discovery that provides an explanation of the text of the law so that the scope of the rule is applied to the event. Result: The validity of an agreement based on the Civil Code is that it fulfills the terms of the agreement in article 1320 of the Civil Code. Limitation: This research only discusses agreements, especially regarding the validity of an agreement according to the Civil Code. Contribution: This research can be used as appropriate, to become a reference in further research.